2018
DOI: 10.1175/jcli-d-17-0563.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Relative Importance of Direct and Indirect Biophysical Effects of Deforestation on Surface Temperature and Teleconnections

Abstract: In this study, the authors linearize the surface energy budget equation that disentangles indirect effects (resulting from changes in downward shortwave and longwave radiation and air temperature) from direct biophysical effects (resulting from changes in surface albedo, evapotranspiration, and roughness length) of deforestation on land surface temperature. This formulation is applied to idealized deforestation simulations from two climate models and to realistic land-use and land-cover change (LULCC) simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 53 publications
7
72
0
2
Order By: Relevance
“…Greening can also trigger a series of changes through atmospheric circulation that indirectly affect the surface temperature 154 . For example, the additionally transpired water enhances atmospheric water vapour content, which results in more longwave solar radiation entrapment and re-emission in the atmosphere, but reduces the amount of shortwave solar radiation reaching the Earth's surface through increased cloud formation 19,155,156 (Fig. 7).…”
Section: Wwwnaturecom/natrevearthenvironmentioning
confidence: 99%
“…Greening can also trigger a series of changes through atmospheric circulation that indirectly affect the surface temperature 154 . For example, the additionally transpired water enhances atmospheric water vapour content, which results in more longwave solar radiation entrapment and re-emission in the atmosphere, but reduces the amount of shortwave solar radiation reaching the Earth's surface through increased cloud formation 19,155,156 (Fig. 7).…”
Section: Wwwnaturecom/natrevearthenvironmentioning
confidence: 99%
“…Forest change can significantly affect surface temperature, and the area, magnitude, and direction of any changes vary significantly from local to global scales [7,17,18]. Some studies have found the inconsistent warming or cooling effects of forest change on temperature [7,[19][20][21]. For example, forest cooling becomes more obvious as latitude decreases, but planted forests replacing natural forests will reduce ET and thus reduce biophysical cooling [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lower height of the vegetation canopy in agriculture versus forest or savanna reduces land surface roughness, increasing aerodynamic resistance, and impeding turbulent exchange with the atmosphere. Consequently, the loss of natural ecosystems in the tropics results in a land surface that tends to warm faster and dissipate heat less effectively than a comparable area of intact tropical forest or woody savanna (Feddema et al 2005, Ban-Weiss et al 2011, Devaraju et al 2018. Of the myriad consequences such changes have for the climate, we focus on one; changes in daily maximum temperatures.…”
Section: Introductionmentioning
confidence: 99%